SHELL LIFE TIME ANALYSIS FOR INSPECTION PLANNING OF HEAT EXCHANGER OIL REFINERY - Suryono, Ahmad Fauzan (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2019)
Heat exchanger is a device where there is a flow of heat transfer between two or more fluids at different temperatures, where both fluids flow in the system. Fluids with a higher temperature will transfer heat to a lower temperature fluid. The shell and tube type is chosen because it has a good mechanical arrangement with a form that is good enough for pressurized operations. Many factors that affect the life span of a heat exchanger include thickness, the rate of reduction in shell thickness and corrosion rate. In this study, the calculation of the corrosion rate is a variable to get the value of remaining life in order to find out whether the shell is still feasible to use. And also know the limits of the process from the shell for further inspections obtained after performing minimum thickness calculations and MAWP. In this calculation carried out using International Standards namely API 660 and ASME Section VIII Division I with material ASTM A-285 Grd CFrom the results of calculations and analysis it was found that the estimated corrosion that occurred in the shell and tube heat exchanger 6-2A at the oil refinery for 14 years (2001 to 2015) amounted to 0.0857 mm/year and the Remaining Life (RL) which is 156.17 years. From these results it was concluded that the shell was feasible to be used until the year 2171. In addition, the MAWP value was also obtained at 5.414 MPa.